A prospective randomised comparison of 2 skin closure techniques in primary total hip arthroplasty surgery. Issue 1 (January 2018) - Rui, Min; Zheng, Xin; Sun, Shao-song; Li, Cheng-yu; Zhang, Xing-chen; Guo, Kai-jin; Zhao, Feng-chao; Pang, Yong
Introduction: As an essential step of total hip arthroplasty (THA), an effective and secure skin closure technique after primary THA is important. Metallic staples closure and subcuticular suture are the 2 common techniques for skin closure. However, which closure technique is the optimal skin-closure method remains unclear. The purpose of this prospective randomised clinical study was to compare the clinical outcomes and costs between staples and subcuticular suture techniques. Methods: In this clinical study, 165 patients who underwent primary unilateral THA through a posterolateral approach from August 2014 to May 2015 were included. According to skin closure technique, the patients were randomised into staples group (interrupted suture with staples, 83 cases) and sutures group (running 4-0 absorbable subcuticular suture, 82 cases). The same operative and perioperative care were provided to all patients. The surgical site infections (SSIs) rate, closure time, time to dry wounds and postoperative hospital stay were recorded and compared. Besides, cosmetic results and patient's satisfaction were evaluated with Hollander wound evaluation score (HWES) and VAS score at postoperative 3 months follow-up respectively. Relative total costs were recorded as well. Results: It was shown that no infections developed in sutures group, while 2 postoperative superficial infections (2.4%) occurred in the staples group. There was a statistically significant difference in the time to dry surgical incisions and postoperative hospital stay favoring sutures (4.8 vs. 5.0 days, p = 0.028; 6.0 vs. 12.0 days, p<0.001, respectively). The cutaneous incision closure using staples consumed significantly less time than that with subcuticular suture (24.7 vs. 357.7 seconds, p<0.001). Moreover, there was no significant difference in HWES and patient's satisfaction between the 2 groups. Finally, the application of subcuticular suture saved an average of $82.2 per case. Conclusions: Closure with running subcuticular suture is cheaper and appears to have a clinical advantage when compared with metallic staples skin closure in primary THA surgery. However, additional operating time may be incurred.